Metabolic syndrome - changes in diagnostic criteria - Cituk, Marta; Jeznach-Steinhagen, Anna; Sińska, Beata (Przewodnik Lekarza/Guide for GPs, 2007)
Metabolic syndrome is a common disorder characterized by metabolic and hormonal dysfunctions. Metabolic syndrome is considered to increase the risk of diabetes and cardiovascular morbidity and mortality. The objective of this study was to present of changes in the definition and the prevalence of metabolic syndrome. Observations continued by scientists throughout the world confirm that the epidemic of metabolic syndrome is increasing. According to data from 2005 5.8 million adult Poles have symptoms of metabolic syndrome.